Pelvic floor symptom progression increases risk for depression, while better physical performance is protective in Asian midlife women - Beverly Wen Xin Wong; Stephen F. Smagula; Liang Shen; Yiong Huak Chan; Jane A. Cauley; Eu-Leong Yong (Scientific Reports)
Abstract There is a lack of studies examining the role of women-specific factors in the development of depression in midlife women. Healthy women (45–69 years) were enrolled at baseline from a Singapore tertiary hospital and followed up 6.8 years later. Risk factors were ascertained using validated questionnaires, and physical performance was objectively measured. Changes in risk factors were calculated by subtracting baseline from follow-up values. Depressive symptoms were defined using a Center for Epidemiological Studies-Depression (CES-D) scale score ≥ 16 and/or use of anti-depression medication. Incident cases were new cases that emerged during follow-up. Modified Poisson regression analyses examined associations between risk factors and outcomes. After 6.8 years, depression developed in 131/825 (15.9%) participants. Improvements (1-standard deviation (SD)) increases in balance (adjusted relative risks, aRR:0.79, 95% confidence interval, CI:0.67–0.94), and one-SD increases in overall physical performance scores (0.80, 0.69–0.93) reduced risks for depression onset. Worsening menopausal symptom severity (1.91, 1.64–2.23) and pelvic floor dysfunction symptoms (1.53, 1.36–1.72) over 6.8 years increased depression risks, independent of age, ethnicity, education, marital status, hypertension, body mass index, baseline exposure and baseline CES-D levels. Worsening menopausal symptoms, pelvic floor dysfunction, and physical performance elevated depression risk, highlighting the need for early detection and intervention.